The need for quality improvement in diagnosing pregnancy induced hypertension in Sri Lanka (South East Asia Journal of Public Health, 2013)
Sri Lanka has shown relatively good maternal outcome indicators for a developing country. However, high maternal deaths from pregnancy induced hypertension and pre-eclamptic toxemia raise questions about the quality of detection and treatment at field antenatal clinics, which is the primary care setting for pregnant women. The objective of the study was to assess the quality of facilities and services provided at the field antenatal clinics to di-agnose pregnancy induced hypertension or pre-eclamptic toxemia. It was a cross-sectional study. This study was set in field antenatal clinics and was conducted in two stages based on the Lot Quality Assurance Sampling method. In the first stage 55 antenatal clinics were selected from 11 Medical officers of Health areas, and in the second stage 275 pregnant women were recruited from these 55 clinics. Quality of services and quality of facilities were assessed using observation checklists. The quality of facilities was better than the quality of services in the Colombo district. The quality of facilities was acceptable in all areas other than for the presence of the Medical Officer. The quality of services was unacceptable in all areas for history taking and examination. Investigation for urine albumin was also unacceptable in all the areas. The sensitivity for measuring the systolic blood pressure and the diastolic blood pressure were 57% (95% CI: 47.4%66.8%) and 16.7% (95% CI: 9.4%24%) respectively. Urgent steps should be taken to improve the quality of care in the substandard areas to reduce the leading cause of maternal mortality in Sri Lanka. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15952 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 55-60